Copolymerization of Functional Norbornenes Catalyzed by Pd Complexes: Is it Living? - Lee, Dong Jin; Choi, Won Ho; Kim, Myungwoong; Kim, Chan Kyung; Lee, Ik Mo (Bulletin of the Korean Chemical Society, 2020)
Copolymerization of functional norbornenes by novel palladium complexes has been successfully done. Soluble addition polymerization products with high Mn and low Đ have been obtained, which improves possible processibility. Some clues of living character of this catalytic system have been observed by kinetic studies of the polymerization and sequential addition of same or different monomers. Copolymerization of Functional Norbornenes Catalyzed by Pd complexes